Global tuberculosis report 2015 - Anderson, Laura (World Health Organization, 2015)
The designations employed and the presentation of the material in this publication do not imply the expression of anny opinion whatsoever on the part of the World Health Organization concerning the legal status of any country, territory,city or area or of its authorities, or concerning the delimitation of its frontiers or boundaries. Dotted and dashed lines on mpas represent approcimate border lines for which there mary not yet be full agreement